IMPACT OF EDUCATION AND HEALTH ON THE UNEMPLOYMENT RATE AND ECONOMY OF EAST JAVA (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
East Java statistics indicate that the total population of East Java Province is increasing every year. The increase in the population is followed by an increase in social problems, including unemployment. The unemployment rate can affect the economy of the society. Efforts must be made to reduce it by improving the quality of society through factors related to education and health. According to data from East Java in 2017, East Java's education has a significant positive direct effect on the East Java economy of 0.343%, while indirectly through unemployment has an insignificant effect increased by 0.0021%. In addition, health has no significant direct and indirect effect on the East Java economy with coefficients of 0.078% and -0.0023%, respectively.